The Role of White Blood Cells in Acute Coronary Syndrome - Shawki, Hilal B. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Inflammation has been shown to play a role in atherosclerosis and acute coronary syndromes. An elevated total WBC count has been associated with increased cardiovascular risk, but which leukocyte subtypes carry this risk. is uncertain. This study was designed to determine the effect of WBC count and other inflammatory markers on severity and outcome of patients with UA/NSTEMI. Patients and Methods: Seventy (70) patients with UA / NSTEMI admitted to CCU at the Iraqi Center for Heart Diseases were subjected to thorough history and physical examination and WBC indices to find their relation to clinical severity and outcome for both in-hospital and/month after discharge. The results were compared with other thirty (30) patients with chronic stable angina and thirty (30) healthy Fac Med Baghdad persons as two control groups. Results: High total baseline total WBC was more prevalent in patient with UA/NSTEMI than in those with stable angina and normal persons (94.1%, 5.9%. and 0%) respectively. High baseline neutrophil was found only in those with UA./NSTEMI (100%, 0%, and 0%). High baseline Neutrophil/lymphocyte (N/L ratio) and Positive CRP were more prevalent in patients with UA/NSTEMI than in other two groups (92.3%. 7.7%. 0%) and (98.5%, 1 .5%. 0%) respectively. Higher total baseline WBC count was significantly found in more severe Braunwald’s class of those with UA/NSTEMI 6.3%. 31.3%. and 50.5% for patients with class I, II, III respectively. The same was true for baseline high neutrophil count (6.7%. 33.3% to 60%), high Baseline N/L ratio (7.7%, 15%. and 21.6%). Patient in the UA/NSTEMI group with higher baseline WBC count had higher risk for death as compared to those of low and intermediate WBC count (0.00%. 0.00%. and 100.00%). The same was true for those with higher baseline neutrophil count (0.00%. 1.90%, 20.00%) and those with higher baseline N/L ratio (0.00%. 25.000%. 75.000%) respectively. Conclusions: Total baseline WBC and differential count is simple, cheap and widely available bedside test that predicted the severity of CAD and one month survival.